Activist scholar selected works of Marilyn Gittell - Gittell, Marilyn; Gittell, Ross J., 1957-; Newman, Kathe; Sage eBooks (Los Angeles : SAGE, 2012)
This title highlights Professor Gittell's writings on community organizations, citizen participation, urban politics, the politics of education, and gender. She specialized in applied and comparative research on local, regional, national, and international policies and politics, and placed a high priority on training researchers and scholars.
Includes bibliographical references.
Specialized.
Description based on print version record.
Keywords: Gittell, Marilyn; Social participation -- Research; Political participation -- Research; Communities -- Research; Electronic books